“There isn’t much support given”: Rural teachers’ perception of curriculum implementation - Kevin L. Teise; Redouane Y. Februarie (International Journal of Educational Management and Development Studies)
The schools in rural areas of the Northern Cape province in South Africa face many challenges that hamper the effective implementation of the mathematics curriculum and, as such, the quality of mathematics education and its learning outcome. To improve the situation, rural teachers should be supported to ensure the successful implementation of the grade 9 mathematics curriculum, in particular. Such support would enable teachers to, despite the challenges, create an effective teaching and learning environment that will positively impact learner success. In this article, we report on rural teachers’ perceptions of the nature and extent of support they need and receive to implement the grade 9 mathematics curriculum effectively. We followed a qualitative approach guided by a case study design. Data were collected through semi-structured interviews with six grade 9 mathematics teachers from the Northern Cape province and were analysed thematically. Findings revealed that whilst some level of support is provided to the teachers, this is insufficient and often irrelevant to the rural education context. Some recommendations are made to enhance the extent and nature of support to the teachers to implement the mathematics curriculum effectively.